We teachers, you fools: Pro + N(P) constructions in Functional Discourse Grammar. (January 2016) - Keizer, Evelien
Abstract: This paper provides a description and analysis of a number of English sequences of pronoun and noun (phrase), such as we teachers, you guys, you fools and them people . On the basis of a close examination of the formal and functional behaviour of authentic examples, it is shown that despite the superficial similarity among these sequences at least four types of construction can be distinguished. One of these types, it is argued, is best regarded as a subtype of apposition, as its members (e.g. we teachers ) exhibit both the formal features and the discourse functions of close appositions. The other three construction types are subsequently characterized as expressions of second person plural (e.g. you guys ), vocatives (e.g. you fools ) and expressions with a pronominal determiner (e.g. them people ). Finally, a Functional Discourse Grammar analysis is provided which reflects the distinctive formal and functional properties of each type of construction, while at the same time bringing out the similarities between each of these constructions and other types of nominal construction.